2019
DOI: 10.1007/s10826-019-01687-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental Solicitation and Adolescents’ Information Management: The Moderating Role of Autonomy-Supportive Parenting

Abstract: Informed consent: Informed consent was obtained from all individual participants included in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
3
14
0
Order By: Relevance
“…As shown in previous work (Baudat et al, 2020), adolescents keeping the highest levels of secrets from their parents at the beginning of middle adolescence also perceived more controlling parenting. Moreover, adolescents who reported a greater increase in secrecy experienced a greater increase in controlling parenting.…”
Section: Associations Between Changes In Secrecy and Controlling Paresupporting
confidence: 72%
See 3 more Smart Citations
“…As shown in previous work (Baudat et al, 2020), adolescents keeping the highest levels of secrets from their parents at the beginning of middle adolescence also perceived more controlling parenting. Moreover, adolescents who reported a greater increase in secrecy experienced a greater increase in controlling parenting.…”
Section: Associations Between Changes In Secrecy and Controlling Paresupporting
confidence: 72%
“…In this context, keeping secrets may be particularly helpful for adolescents as a means of expressing resistance to their parents (Parkin & Kuczynski, 2012). In line with these propositions, controlling parenting behaviors have been cross-sectionally associated with lower levels of disclosure (through lower levels of need satisfaction ;Tokić Milaković et al, 2017) and greater secrecy among middle adolescents (Baudat et al, 2020). Similarly, it has been longitudinally shown that when parents reacted in a controlling manner to their child's disclosure (e.g., by being cold and rejecting the child's feelings), adolescents felt more controlled, which, in turn, triggered them to keep more secrets (Tilton-Weaver et al, 2010).…”
Section: Secrecy Within the Parent-child Relationship: The Case Of Comentioning
confidence: 81%
See 2 more Smart Citations
“…Parents' asking questions about adolescents' activities as well as about their relationships with friends, could be perceived by adolescents as an attempt to be involved in adolescents' lives. When perceived as such, parental solicitation elicits disclosure in adolescents (Baudat et al 2020), which in turn gives parents opportunities to provide support and ease adolescent emotional distress. Indeed, parental involvement is linked to improved self-esteem and emotional self-regulation skills, which in turn are protective against the development of depressive symptoms (Flouri and Buchanan 2003).…”
Section: Discussionmentioning
confidence: 99%